2015
DOI: 10.21608/jappmu.2016.52726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Betaine Supplementation to Methionine Adequate Diet on Growth Performance, Carcass Characteristics, Some Blood Parameters and Economic Efficiency of Broilers

Abstract: The objective of this study was to evaluate the influence of supplementing betaine to broiler diets containing adequate concentration of methionine on growth performance, carcass traits and some blood parameters, as well as economic efficiency. Two hundred and sixty day-old Ross broiler chicks were allotted into five equal treatments of four equal replications. Five experimental isonitrogenous and isocaloric diets with graded levels of betaine (0.0, 1.0, 1.5, 2.0 and 2.5 g/kg diet) were formulated and fed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
4
6
0
Order By: Relevance
“…In consequence of the findings obtained at the end of the experiment, no statistically significant difference was found between the groups in terms of carcass parameters, and heart, liver, spleen, and gizzard weights in the control and experimental groups. The present study is similar to those by (El-Shinnawy 2015;Honarbakhsh et al, 2007;Uzunoğlu and Yalçın, 2019) reporting that betaine addition did not affect carcass yield and heart, liver, spleen, and gizzard weights.…”
Section: Carcassparameterssupporting
confidence: 92%
“…In consequence of the findings obtained at the end of the experiment, no statistically significant difference was found between the groups in terms of carcass parameters, and heart, liver, spleen, and gizzard weights in the control and experimental groups. The present study is similar to those by (El-Shinnawy 2015;Honarbakhsh et al, 2007;Uzunoğlu and Yalçın, 2019) reporting that betaine addition did not affect carcass yield and heart, liver, spleen, and gizzard weights.…”
Section: Carcassparameterssupporting
confidence: 92%
“…Inconsistance to the present results, Bogusławska et al [34] observed increased plasma TG (18%) of betaine-fed pigs which could affect cholesterol metabolism, furthermore, Martins et al [35] reported significant increase ( P > .05) in blood serum concentrations of triglycerides in response to dietary betaine supplementation in broilers. Betaine might activate liver lipid mobilization and improve hepatic lipoprotein secretion as indicated by El-Shinnawy [36] which supported the strong positive significant correlation between TG and GLB obtained in G3. The trend of serum cholesterol observed in G3 was partially in agreement with Boguslawska et al [34] who reported that betaine supplementation can lead to higher serum cholesterol.…”
Section: Discussionsupporting
confidence: 62%
“…Similar to the present results, some researchers reported that carcass yield (6,12,49) and the relative weights of liver (12,41,49), spleen (12,41,49), heart (49) and bursa of Fabricius (12,49) were not affected by dietary sepiolite. In some studies (4,8,11,13) carcass yield was increased by betaine supplementation. The improvement in carcass yield may be due to the osmotic effects of betaine that increases water retention (45).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in triglyceride could be correlated with betaine usage in shynthesis of carnithine and lecithin for fat immobilization. El-Shinnawy (11) showed that betaine supplementation increased serum cholesterol, protein and albumin. Some researchers (8,15) indicated that betaine supplementation improved the immunity of birds.…”
Section: Discussionmentioning
confidence: 99%